Language Shift in Tamil Ethnics in Lubuk Pakam - Vijay - Khana; Berlin - Sibarani; Busmin - Gurning (LINGUISTIK TERAPAN, 2020)
This research focused on language shift in Tamil Ethnics in Lubuk Pakam. It is aimed at finding out the process of language shift and the reason of the language is shift. The data were taken from the Tamil families living in Lubuk Pakam. This study was based on qualitative research. The subjects of the study were 72 Tamil people in Lubuk Pakam. The subjects were divided into two groups, namely intra marriage and inter marriage of Tamil people in Lubuk Pakam. Questionnaires and interviews were used to gain the data. The data were analyzed by using data collection, data reduction, data display and data verification. The findings show that there are five domains, which influence the process of language shift into Bahasa Indonesia of second and third generation in intra marriages and intermarriages of Tamil ethnics, namely family, friends, education, religion and employment. The status of Bahasa Indonesia as the official language and social success are the reasons for first generation of intra marriages and inter marriages Tamil ethnics shift into Indonesian language mean while in third generation the status of Bahasa Indonesia, social success and language use since child as the reason of Tamil ethnics shift into Bahasa Indonesia.Keywords: Language Shift, Domains, Tamil, Ethnics